Application of Good Corporate Governance Principles to the Quality of Financial Statements - Thadeus Fransesco Quelmo Patty; Pipiet Niken Aurelia; Siktania Maria Diliana (Neo Journal of economy and social humanities, 2023)
This study aims to determine the effect of the application of good corporate governance principles on the quality of financial statements of the Wair Pu'an Drinking Water Regional Public Company, Sikka Regency. The data collection technique in this study used questionnaires distributed by 64 employees which were then processed using the SPSS 25 program. The analytical method for testing hypotheses is multiple linear regression analysis. The results of the statistical test t (partial) show that Transparency (X1) has a significant effect on the quality of financial statements (Y), Accountability (X2) has a significant effect on the quality of financial statements (Y), Accountability (X3) has a significant effect on the quality of financial statements (Y), independence (X4) has an insignificant effect on the quality of financial statements (Y), fairness (X5) has an insignificant effect on the quality of financial statements (Y). Based on statistical test F (simultaneous) shows that Transparency (X1), Accountability (X2), Accountability (X3), Independence (X4), and Fairness (X5) have a significant effect on the Quality of Financial Statements.